2019
DOI: 10.2174/2210327909666190611142348
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Amplification Damping Using a DSTATCOM-based Artificial Intelligence Controller

Abstract: Background & Objective: Harmonic amplification is one of the primary issues in power system networks. The objective of this study is to manage the harmonic event and its significant effects on power quality. A new control approach that uses Artificial Intelligence (AI) is proposed and applied to a Distribution Static Synchronous Compensator (DSTATCOM). DSTATCOM is a FACTS device that can achieve highly effective reactive power compensation to reduce and/or damp the harmonic amplification in power system ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Weighted numbers are utilized to weight the acceleration. In (9) presents the velocity vector [24,25].…”
Section: Hybrid Algorithm Particle Swarm Optimization-neural Network (Pso-nn) For Ptsimentioning
confidence: 99%
“…Weighted numbers are utilized to weight the acceleration. In (9) presents the velocity vector [24,25].…”
Section: Hybrid Algorithm Particle Swarm Optimization-neural Network (Pso-nn) For Ptsimentioning
confidence: 99%
“…One of the forms of power quality issues is the harmonics problem [13]. A DSTATCOM controller based on discrete-time multilayer neural networks was described.…”
Section: Introductionmentioning
confidence: 99%
“…In [10], FACTS devices were utilised to improve power system operation control, and PMU was used as a monitor to improve the capability of state estimation systems and full observable systems. The stability of a power system is a crucial area of research to describe the harmonics problem, and many studies employ FACT devices, such as DSTATCOM, as shown in [11,12]. State estimation is extremely important in a power distribution system for determining the variable state in a system network, as shown in [13].…”
Section: Introductionmentioning
confidence: 99%